Development of semi-instant glass batch for increasing glass melting efficiency - Tapasa, Kanit; Meechoowas, Ekarat (Bulletin of Applied Sciences, 2022)
The energy reduction of glass melting can be carried out by modifying glass batch using low-enthalpy raw materials or transforming typical loose powder batches into preheated granule batches, which are herein called "Semi-Instant Glass Batch (SGB)”. The SGB can be melted faster than loose powder batches because the water and CO2 in raw materials have already been eliminated. The surface areas of the SGB that contacts to heat also increases resulting in better heat conductivity, therefore the melting time decreases. The purpose of this work was to produce the SGB by granulation. The ground glass batch was granulated by using Na-CMC as binder agent, in which, the suitable viscosity was determined. It was found that the best ratio of agent/solution was 25 g/100ml water. The melting efficiency was studied by the Batch-Free-Time experiments. The results showed that the SGB performed the better melting efficiency than the loose powder batch and the bigger size of SGB effects on the better of melting efficiency.